«Lumière et lumière» dans trois Vies de saints: Étienne le Jeune, Constantin-Cyrille, Clément d'Ochrida - Devos, Paul (Analecta Bollandiana, 1993)
An expression about 'light added to light' already found with a general meaning in Gregory of Nazianzus' Discourses I and II, occurs also with a specific sense (first light = baptism; second light = monastic vows), in both the Greek Vitae of St Stephen the Younger and St Clement of Achrida and in the Slavic Vita of St Constantine-Cyril; St Stephen's Life is particularly 'enlightening' on the subject.